Nitrogen fertilizations via leaf on soybean stages and nitrogen released on yield of off season maize - I. V. A. Fiorini; C. S. Pereira; A. A. Silva; E. L. Resende; H. D. Pereira (Scientific Electronic Archives, 2020)
The objective of this study was to evaluate the residual effects of nitrogen (N) fertilization liberation of mulching soybean crop in the yield corn of-season. The sowed was the corn hybrid Land® in date 01/26/2017, of mulching soybean crop experiment, in Sinop-MT, Brazil. The experimental design was a randomized complete block with four replications with teen treatments. The treatments were: control without N application (only inoculated with Bradyrhizobium japonicum e B. elkanii) and the other treatments was applied the dose of 10 kg ha-1 of N in different phenological stages and modes of application (the cover in the sowing; in V2 the haul in coverage; in V2 via leaf; in V4 the haul in coverage; in V4 via leaf; at R1 the coverage haul; in R1 via leaf; in R2 the cover and R2 in the leaf). The traits components of the yield analyzed were: number of rows of grain, number of grains per rows, the thousand-grain weight and yield grains. The mineralization of the nitrogen provenient of mulch the soybean crop is not sufficiency for corn off-season crop. The application of nitrogen in the stages V2 and R1 in coverage in the soybean predecessor crop provided the highest values to yield grains of the maize off-season crop.